Impact of Coronavirus (COVID-19) on Pregnancy and Childbirth (Mothers and Babies) Literature Review - Ripursari, Tety; Suhita, Byba Melda (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The literature study aims to determine the impact of coronavirus on pregnancy and childbirth, namely on mothers and babies. In this literature study, three database (Wiley, PubMed, Google Scholar) were used to select studies covering the last five years and English journals, titles, and abstracts. The search results obtained eight journals that match the inclusion criteria and for an average number of participants more than one hundred in each study. Coronavirus (COVID-19) in pregnancy and childbirth can have an impact on the mother (premature, premature rupture of membranes, hypoxia, abortion, preeclampsia, ectopic pregnancy and death), whereas in infants it can cause asphyxia, LBW, fetal distress, stunted fetal growth, meconium aspiration syndrome, neonatal seizures, neonatal death, IUFD, and no mother-to-fetus transmission